HOMOGENEOUS VINYLATION OF 2-HYDROXY-2 PHENYLETHANICAL ACID - A.B., Parmanov; S.E., Nurmanov; Maniecki, Tomash; O.E., Ziyadullayev; J.U., Abdullayev (International Journal of Research -GRANTHAALAYAH, 2018)
Homogeneous-catalytical vinylation of 2-hydroxy-2-phenylethanical acid was carried out. Influence of catalylists nature, temperature and duration reaction on yield of synthesized vinyl ester has been investigated. basis of natural raw materials. Based on vinyl esters of carboxylic acids, their polymers and copolymers with unsaturated compounds of the ethylene series, emulsifiers for emulsion paints have been obtained; compounds that improve the viscosity of lubricating oils and are used as crosslinking agents in the rubber industry. Synthesis of vinyl esters based on monobasic aliphatic acids has been studied by the example of acetic acid by many researchers. In this respect, the aromatic carboxylic acids remain unexplored. Goal: Synthesis of vinyl ester of mandelic acid by it’s reaction with acetylene in the presence of heterogeneous catalysts, investigation of the influence of the nature of catalysts and the reaction temperature on the yield of obtained product. Methodology: Catalytic systems based on AlCl3∙6H2O or zinc salt of mandelic acid with dimethylsulfoxide were prepared and heterogeneous catalytic vinylation of mandelic acid with acetylene was carried out and it’s vinyl ether was obtained. Scientific Novelty. The synthesis of vinyl ester of mandelic acid with it’s reactions with acetylene using the catalytic systems AlCl3∙6H2O-DMSO and (C6H5CH(OH)COO)2Zn-DMSO was carried out. Obtained Data: The vinyl ester of mandelic acid was synthesized by it’s vinylation in stationary heterogeneous conditions. The influence of the nature of the catalyst (AlCl3∙6H2O, (C6H5CH(OH)COO)2Zn), temperature and duration of the reaction on the yield of the product was investigated. Features: vinylation of hydroxy carboxylic acid was investigated; the catalytic systems AlCl3∙6H2O-DMSO and (C6H5CH(OH)COO)2Zn-DMSO are used; factors influencing the yield of vinyl ester of mindalic acid and optimal conditions of it’s synthesis were found.